Subsidizing quantity donations: matches, rebates, and discounts compared - Diederich, Johannes; Eckel, Catherine C.; Epperson, Raphael; Goeschl, Timo; Grossman, Philip Johnson (Jahrestagung 2019 / Verein für Socialpolitik C14, Session: Public Economics III, 2019)
We present online-experimental evidence that challenges the generalizability of established results on subsidizing giving by considering a "quantity donation" scheme. We define this scheme as one in which donors choose how many units of a charitable good to fund, rather than the amount of money to give. We find that different subsidy types are equally effective in raising funds. This contrasts with the common result of matches being superior to rebates. The finding masks a higher likelihood of giving under rebates and larger donations under matches and discounts. Our results emphasize the role of small changes in the donation environment.